Footprints of past earthquakes revealed in the afterslip of the 2010 Mw 7.8 Mentawai tsunami earthquake - Feng, Lujia (2017)
The 2010 Mw 7.8 Mentawai tsunami earthquake marks one of the first tsunami earthquakes to have postseismic deformation observed by geodetic instruments. The Sumatran GPS Array has recorded the postseismic deformation following this event continuously for >5 years. The spatiotemporal evolution of the postseismic deformation is well explained by velocity-strengthening frictional sliding on the Sunda megathrust. Our results show that the 2010 afterslip progressed downdip relative to the 2010 coseismic rupture. The southeastern portion of the afterslip region overlaps the area that slipped during the main shock and afterslip of the 2007 Mw 8.4 Bengkulu earthquake, while the northwestern portion slipped an area without recent large earthquakes. By incorporating pre-earthquake stress conditions into quasi-dynamic models, we demonstrate that the preceding cumulative slip from the 2007 sequence might have caused a ∼0.1 MPa difference in pre-earthquake Coulomb stress between the southeastern and northwestern portions of the afterslip region.